HANAFIY FIQHINING ILK NAZARIY ASOSLARI - Sobirjonova Zilola (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract. Although the foundations of Sharia are based on the Qur'an and Sunna, it  has  undergone  developmental  stages  like  other  legal  systems.  Various  historical factors, including natural and climatic conditions, living standards, political and social structures,  and  the  expansion  of  Islam  into  diverse  cultural  and  ethnic  regions, contributed to the evolution of Sharia. During the first three centuries, these influences shaped Islamic governance, institutions, and legal principles.